YIIFSWA II - Implementation planning workshops - Day 3 - closing plenary session - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2017)
Day 3 and closing of the plenary session of YIIFSWA II launch and Implementation planning workshops in IITA Ibadan